Distance learning for Agritex - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Department of Agricultural Technical and Extension Services (Agritex), Zimbabwe, has introduced an innovative staff training project. Although Agritex staff have wide gad experience, it is considered important that their expertise in the...